PROPOSAL OF A METHODOLOGY OF CRITERIAL ASSESSMENT OF TECHNICAL INDICATORS FOR THE PURPOSE OF SELECTING AN OPTIMAL SEMI-TRAILER TRACTOR FOR THE NEEDS OF A TRANSPORT COMPANY - Miroslav BLATNICKÝ; Ján DIŽO; Alyona LOVSKA (Scientific Journal of Silesian University of Technology. Series Transport)
The goal of this work is to describe the current state of road freight transport from the point of view of the entrepreneur and the owner of semi-trailer tractors within the Slovak Republic. The article contains a brief description of freight transport works and points out the individual aspects of doing business in this sphere in Slovakia. In the next one, an original criterion evaluation program is created in the MS Excel application for semi-trailer tractors. In this program, an owner, a future owner, or a driver of a tractor can compare any number of tractors. Subsequently, based on the point evaluation, the program determines, which tractor in the comparison has more points and, therefore, it is more suitable for business activity. A sample comparison will be made on two tractors (Swedish and German brands) operated by a commercial transport company. The parameters of the tractors given, checked and calculated by the manufacturer are implemented in the criterion evaluation program. In the criterion evaluation, a tractor of one brand scored more points and therefore won. All knowledge, results, and conclusions found in the work are discussed with the management of a commercial transport company and its drivers. Based on the findings and results achieved, it can be concluded that the criterion evaluation program is extremely suitable for the application of any tractor, any brand, and thus the condition of the repeatability of the experiments is guaranteed. Based on these aspects, all the objectives of the work were fulfilled, and thus the result of the research is suitable as a decision-making aid for the purchase of a tractor for the future owner.